Bacterial coinfection in influenza pneumonia: Rates, pathogens, and outcomes. (23rd February 2022) - Bartley, Patricia S.; Deshpande, Abhishek; Yu, Pei-Chun; Klompas, Michael; Haessler, Sarah D.; Imrey, Peter B.; Zilberberg, Marya D.; Rothberg, Michael B.
Abstract: Background: Evidence from pandemics suggests that influenza is often associated with bacterial coinfection. Among patients hospitalized for influenza pneumonia, we report the rate of coinfection and distribution of pathogens, and we compare outcomes of patients with and without bacterial coinfection. Methods: We included adults admitted with community-acquired pneumonia (CAP) and tested for influenza from 2010 to 2015 at 179 US hospitals participating in the Premier database. Pneumonia was identified using an International Classification of Disease, Ninth Revision, Clinical Modification (ICD-9-CM) algorithm. We used multiple logistic and gamma-generalized linear mixed models to assess the relationships between coinfection and inpatient mortality, intensive care unit (ICU) admission, length of stay, and cost. Results: Among 38, 665 patients hospitalized with CAP and tested for influenza, 4, 313 (11.2%) were positive. In the first 3 hospital days, patients with influenza were less likely than those without to have a positive culture (10.3% vs 16.2%; P < .001), and cultures were more likely to contain Staphylococcus aureus (34.2% vs 28.2%; P = .007) and less likely to contain Streptococcus pneumoniae (24.9% vs 31.0%; P = .008). Of S. aureus isolates, 42.8% were methicillin resistant among influenza patients versus 53.2% among those without influenza ( P = .01). After hospital day 3, pathogens for both groups were similar. Bacterial coinfection was associated with increased odds of in-hospital mortality (aOR, 3.00; 95% CI, 2.17–4.16), late ICU transfer (aOR, 2.83; 95% CI, 1.98–4.04), and higher cost (risk-adjusted mean multiplier, 1.77; 95% CI, 1.59–1.96). Conclusions: In a large US inpatient sample hospitalized with influenza and CAP, S. aureus was the most frequent cause of bacterial coinfection. Coinfection was associated with worse outcomes and higher costs.